Related Knowledge of Nurses Acute Coronary Syndrome with Accuracy of Patiens Do Help According to SOP Acute Coronary Syndrome - Wahyuni, Lutfi; saudah, Noer saudah; Nurmilasari, Hanik (Health Notions, 2017)
Acute Coronary syndrome is one of the syndromes that often caused a sudden death, so it is an emergency problem that needs fast response. Knowledge is the result of knowing and it appears after someone observing to a certain object. The purpose of this research was to find out the correlation between nurse knowledge about Acute Coronary Syndrome with precise action to help according to Acute Coronary Syndrome SOP. The method that been used in this research was analytic correlation with cross sectional approach. The sample of this research was all 26th nurse at ICCU of Sidoarjo hospital. Data collection was questionnaire form to observe the nurse knowledge about Acute Coronary Syndrome and observation form to observe the precise action done by the nurse to help. The result of cross tabulation showing the knowledge of âgoodâ categories was 12 people, 11 people was doing the right help and 1 people was wrong. The nurse knowledge on âenoughâ category was 13 people, 8 people doing the right help and 5 people was wrong. Knowledge on âpoorâ category ws 1 people and does not giving the right help. The result ws showing that there was correlation between the nurse knowledge about Acute Coronary Syndrome with the accuracy of giving help according to the SOP.  It was proven that knowledge can raise the precise action done by the nurse in helping patient according to Acute Coronary Syndrom SOP.